DIDACTIC DESIGN OF LEARNING TO FIND MAIN IDEA OF PARAGRAPH BY USING COOPERATIVE INTEGRATED READING AND COMPOSITION MODEL IN ELEMENTARY SCHOOL - Denovi Luthfiyani; Aan Kusdiana; Seni Apriliya (PEDADIDAKTIKA: Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2014)
To find main idea of  paragraph was one of basic competences in KTSP 2006 that had to be mastered by 4th grade students. Learning process was conducted by using conventional learning and it did not notice to students  developing characteristic, so the student did not motivate to study. It was one of the causes of learning obstacle in learning to find main idea of the paragraph. To minimize learning obstacle happened needed to be created a didactic learning design.  Didactic design was a learing design that was conducted by teacher before learning process, in learning process, and after learning process. Didactic design was arranged by using Cooperative Reading and Composition model ( CIRC). The design noticed student developing characteristic, prediction of student respons toward learning and Pedagogical Didactic Anticipation (ADP) with Hypothetical Learning Trajectory (HLT) for creating expected didactic situation. The approach of this study used was qualitative approach. The approach was descriptive by using Didactical Design Researh (DDR) as the method. The result showed that learning obstacles were descrease significantly in learning to find main idea of paragraph. The students showed up the positive respons in learning because it was suitale with characteristic of students developing. Therefore, didactic design had been arranged and had been implemented successfully in anticipating and minimazing learning obstacles in learning to find main idea of paragraph.